Restoration of finger and thumb movement using one-stage free muscle transplantation. Issue 3 (3rd May 2016) - Hou, Yi; Qin, Bengang; Yang, Jiantao; Li, Xiangming; Yang, Yi; Fu, Guo; Gu, Liqiang; Qi, Jian
Abstract: Objective : Functional reconstruction following severe traumatic muscle loss may cause problems for reconstructive surgeons. In such situations, functioning free muscle transplantation (FFMT) represents an important alternative treatment option. Methods : The clinico-demographic characteristics of 11 patients receiving modified FFMT between 2005–2013 were retrospectively reviewed. The muscle strength, range of joint motion (ROM), total active motion (TAM) of the fingers, and Disability of Arm Shoulder and Hand (DASH) score were adopted to assess the functional results. Results : All FFMTs were performed in the secondary stage. The authors found that the mean ROM, TAM, ratio of TAM compared with the contralateral side, and DASH score were 112 degrees, 150 degrees, 62%, and 22.8, respectively; and eight and nine patients achieved greatly improved grip function and M4 muscle strength, respectively. Conclusion : Using one-stage free muscle transplantation to restore finger and thumb movement simultaneously is an effective method for functional restoration following traumatic multi-muscle loss.